ANALISIS PERBEDAAN KINERJA PEMERINTAH DAERAH YANG DIPIMPIN KEPALA DAERAH BERLATAR BELAKANG ENTREPRENEUR DAN NONENTREPRENEUR - TRIA ANDARI ARNA SARAGIH; SRI MULYANI (Departement of Islamic Banking, Faculty of Islamic Economics and Business, The State of Islamic University (UIN) Sultan Maulana Hasanuddin Banten,, 2018)
AbstractIn the implementation of regional autonomy, the regional head is expected toimplement visionary and innovative leadership patterns to fulfill hisobligations in developing regions, providing quality services, and creatingprosperity of the local community. In this study, the sample used is limited tolocal governments in Sumatera and Java who conducted elections of regionalheads (Pilkada) in 2010 ie as many as 111 provinces, districts, and cities. Thedata used secondary data, namely the score of local government in rankingand performance status of local government, obtained from the website of theMinistry of Home Affairs; and Audit Opinion, as seen in the summary ofaudit report result by the Supreme Audit Board (BPK). The conclusions ofthis study are: 1) there is a difference between the performance of localgovernment in Sumatera and Java, led by the Head of Region entrepreneurand non-entrepreneur background based on score of local government indetermining the rank and status of local government administration; 2) Thereis no difference between the performance of local government in Sumatera andJava led by the head of region with entrepreneur and non-entrepreneurbackground based on audit opinion of Supreme Audit Board (BPK) on LocalGovernment Financial Report (LKPD)